(3QSGdI GdQVi hGdJSdje Edi cGaI GdehMOjfs - (3MeRI Hf Ydj Hf CMeO GdaGQSqj GdMGcej GdOQRj , J (B433 (3g`s
(3ChdgG (B:s
(3hEdi LejY ef Tc ai ehdGfG Ld PcQg hai hdjg bGFe GdReGf Ydjg GdSdGe ef YHO ehdGfG SHMGf bOQI ehdGfG hJYGdi dGghJg s
(3BNQgG (B:s
(3Ch JXfhG Hg Xf GdShA aJchfhG ef GdNGSQjf ai GdOjf hgh MSHi hYdjg JhcdJ hgh fYe GdeYjf JeJ HMeOehdGfG hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B17s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI HgG EWGQGJ s
Keywords: (3abg GdePGgH GdCNQis